Feasibility Investigation: Investment in Artificial Stadium Grass in Nan District, LuangPrabang Province - PHANTHOULACK, Ounheuan; SIPHANTHONG, Bounthavy; PATHOUMTONG, Santi; PHILASOUK, Thatsaphone (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
This study aimed to investigate feasibility of the investment in artificial stadium grass in N a n district, LuangPrabang Province, focusing on marketing, technique, managem ent and finance. Data was collected using the questionnaire with 13 9 participants. The study found that there was a feasibility due to appropriate price setting for seating, beverage, grandstand, bathroom, and changing room. The average revenue was 634,080,000 kip per year. There was also feasibility in technique because the field was covered with standardized artificial stadium grass. There was a snack bar where customers can enjoy foods, drinks and various sport equipment. There was feasibility with regard to management. That was because the investment was private enterprise hiring 3 staff: a manager, a cashier and a cleaner. Relationship and compensation were highly encouraged. Additionally, there was feasibility finance in all 3 cases: (1) funds have been made available within 2 years 9 months with Net present value (NPV) 360,295,747 kip and 27.03% of Internal rate of return (IRR) was identified as highly feasible. (2) funds have been made available within 3 years 1 months with Net present value 226,533,172 kip and 21.75% of Internal rate of return was indicated feasible. (3) funds have been made available within 3 years 7 months with Net present value 535,405 kip and 11.73% of Internal rate of return was indicated less feasible.